2013
DOI: 10.1371/journal.pone.0071286
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium-Phase High Spatial Resolution Contrast-Enhanced MR Angiography at 1.5T in Preoperative Imaging for Perforator Flap Breast Reconstruction

Abstract: ObjectivesThe aim was (i) to evaluate the accuracy of equilibrium-phase high spatial resolution (EP) contrast-enhanced magnetic resonance angiography (CE-MRA) at 1.5T using a blood pool contrast agent for the preoperative evaluation of deep inferior epigastric artery perforator branches (DIEP), and (ii) to compare image quality with conventional first-pass CE-MRA.MethodsTwenty-three consecutive patients were included. All patients underwent preoperative CE-MRA to determine quality and location of DIEP. First-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…16 Of the tests used for identifying perforators as part of the preoperative assessment for a perforator flap surgery, the results using CTA and MRA were well described. [4][5][6] However, the disadvantages of CTA and MRA are high cost, radiation exposure, possible allergic reaction to the contrast agents, and difficulty in detecting small vessels. After the first clinical results following the use of color Doppler US were reported in 1994, technological advancements have enabled us to detect reduced blood flow in superficial vessels with a diameter as small as 0.2 mm using higher-frequency transducers.…”
Section: Discussionmentioning
confidence: 99%
“…16 Of the tests used for identifying perforators as part of the preoperative assessment for a perforator flap surgery, the results using CTA and MRA were well described. [4][5][6] However, the disadvantages of CTA and MRA are high cost, radiation exposure, possible allergic reaction to the contrast agents, and difficulty in detecting small vessels. After the first clinical results following the use of color Doppler US were reported in 1994, technological advancements have enabled us to detect reduced blood flow in superficial vessels with a diameter as small as 0.2 mm using higher-frequency transducers.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have shown accurate localization of perforators with MRA for DIEP flaps [1,15,[32][33][34][35][36][37]. Application of novel MR techniques, such as the use of unenhanced MRA, has shown promise as the vessels can be visualized without intravenous administration of contrast [35].…”
Section: Preoperative Imagingmentioning
confidence: 99%
“…Peripheral arterial disease (PAD), characterized by arteriosclerotic stenosis or occlusion of pelvic and/or lower extremity arteries, may manifest clinically as intermittent claudication or critical limb ischemia (1). The primary treatment for patients with intermittent claudication is supervised exercise therapy, which may stimulate collateral blood artery formation to increase muscle perfusion (1)(2)(3).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Arteriosclerotic peripheral arterial disease (PAD) is a major health care problem among the elderly in the Western society. The estimated prevalence of PAD in the general population is in the range of 3% to 10%, which increases up to 15-20% in persons over 70 years (1)(2)(3)(4). In the Netherlands, the estimated prevalence among persons over 55 years is 19.1%, ranging from 8.1% at the age of 55-59 years towards 55.8% in persons over 85 years (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation